EVALUASI KEBIJAKAN REFORMASI STRUKTUR BIROKRASI PEMERINTAH KECAMATAN (Suatu Studi di Kecamatan Salibabu Kabupaten Kepulauan Talaud) - Mayore, Marsuki (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAK : The purpose of this study was to determine the extent of strucral reform policies of thegovernment bureaucracy districts governed by the PP.No.19 of 2008 to realize the efficiency andeffectiveness of government administration districts,especially in Sub Salibabu Talaud Islands. The methodused is descriptive method-kualitatif. Imforman officials,namely : Head,the District Secretary,Head ofSection (4),Head of Sub Section (2). And plus resdents masyarakat (2). Date collection techniques used wereinterviews.Analysis date is done by a using qualitative analysis interacktive model of Miles and Hubernann.Based on the results of the study conclude : (1) Struktur Salibabu District government bureaucracy ( Theamount of organization and type of organizational units) are in accordance with the policy of reformbureaucratic structures Disrict government stipulated in article 32 PP.No. 41 Year 2007 and PP. No. 19 Year2008 on the district. (2) The structure of district Government Bureaucracy Salibabu meets the criteria ofeffectiveness and efficiency as a mandate PP.No.41 Year 2007,where the duties and functions ( TOR ) asdefined by the District Government can already be carried out by a unit/organization units (sections andsub-sections) which exists. (3) The structure of the Distict Government Bureaucracy Existing Salibabu iseffective enough to be able to realize the effectiveness and efficiency of the of District Government. Based onthe conclusions of the research results it is necessary to put forward suggestions : (1) structural reformpolicies of the Government Bureaucracy District such policy must be consistently in the structuring ofGovernment Bureaucracy District shoul be followed by reform of personnel resources ,and also by theprovision of adequate infrastructure tasks.Keywords : Reform the Bureaucracy Structure of the District Governments.